Saltwater - McLennan, Cathy (University of Queensland Press, 2016)
'Everyone knows that some of those kids are innocent ⁵ your dilemma is not whether the kids are innocent, but which of the kids are innocent.'When Cathy McLennan first steps into Townsville's Aboriginal and Torres Strait Islander Legal Service as a young graduate she isn't expecting a major murder case to land on her desk. The accused are four teenage boys whose family connections stretch across the water to Palm Island. As she battles to prove herself in the courtroom, Cathy realises that the truth is far more complex than she first thought. She starts to question who are the criminals and who are the victims. Saltwater tells the compelling story of one lawyer's fight for justice amongst the beauty and the violence of this tropical paradise.